Personality and relational aggression: Moral disengagement and friendship quality as mediators. (June 2016) - Kokkinos, Constantinos M.; Voulgaridou, Ioanna; Markos, Angelos
Abstract: The present study tested mediation models of relational aggression integrating personality (callous-unemotional traits, behavioral activation system), self-regulatory cognitive processes (moral disengagement), and interpersonal factors (friendship quality) in a non-clinical sample of 276 Greek preadolescents. Relational aggression was positively associated with callous-unemotional traits, behavioral activation system, moral disengagement and negative friendship quality (i.e. conflict and betrayal). Moral disengagement mediated the effects of callous-unemotional traits and behavioral activation system on relational aggression. Furthermore, friendship conflict mediated the link between callous-unemotional traits and relational aggression, while positive friendship the association between behavioral activation and relational aggression. The findings confirm previous research and are discussed in terms of their implications. Highlights: The link between personality and relational aggression was explored among preadolescents Relational aggression was associated with all variables under study Moral disengagement mediated callous-unemotional traits, behavioral activation system, and relational aggression links Friendship conflict mediated the link between callous-unemotional traits and relational aggression Positive friendship traits mediated the link between behavioral activation system and relational aggression